Commonwealth Higher Education Support Scheme: Directory of Available Agencies for Books, Journals and Library Development - Rowbotham, Graham (Commonwealth Secretariat, 1991)
This directory is published by the Commonwealth Secretariat to facilitate books, journals and documentation supply to higher education institutions in developing countries. It is hoped that the array of information presented here will assist these institutions and their staff to locate and approach organisations that can help them meet some of their needs.
Keywords: Higher education